Housing markets and macroeconomic risks - Cavalleri, Maria Chiara (OECD Economics Department Working Papers, 2019)
Housing markets are large and highly volatile: they can thus create large macroeconomic risks. The current paper provides a bird's eye view of where the housing markets of major OECD economies currently stand. It then uses the results of recently developed models to provide indications of where macroeconomic risks exist. Finally, the paper draws on recent empirical analyses to suggest how economic policies can enhance economic resilience by reducing housing-related risks through macroprudential measures and housing market reforms (such as changes in rent regulation, taxation and land use policies)